The Effectiveness of Investing in Stock Exchange Markets in Central and Eastern European Countries with Regard to NYSE2‑LSE‑HKSE2. a Comparative Risk Analysis - Jacek Pera (Comparative Economic Research. Central and Eastern Europe, 2019)
The aim of this paper is to assess the effectiveness and risk in the stock exchange market in Central and Eastern Europe countries (CEE) in view of the largest stock exchanges: NYSE2-LSE-HKSE2. The implementation of this objective was based on an analysis of basic stock market indicators and a discussion of the investment effectiveness of the stock exchange and the risk and investment effectiveness analysis in the stock exchange market in CEE with regard to NYSE2-LSE-HKSE2 - assumptions, test method, tests results. The following working hypothesis was adopted in the analysis: Despite high vulnerability to investment risk, the stock exchanges in CEE, due to dynamic development, are improving their investment position with regard to global stock exchanges. The relative indices of stock market attractiveness and an autoregressive model for forecasting changes in the stock market index were used to verify this thesis. The results from the tests make it possible to state that the stock exchanges in CEE are constantly improving their position with regard to operational effectiveness and risk mitigation when compared to the largest global stock exchanges analysed, ambitiously striving to become significant financial centres within Europe and worldwide.
Keywords: C1; C5; F3; G1; 330; index; ratio; securities; stock exchange; risk